Proton, muon and 13C hyperfine coupling constants of C60X and C70X (X = H, Mu). Issue 3 (2nd December 2014) - Brodovitch, Jean-Claude; Addison-Jones, Brenda; Ghandi, Khashayar; McKenzie, Iain; Percival, Paul W.
Abstract : Four of the five possible C70 H radicals are formed when H atoms add to fullerene C70 . Their 13 C hyperfine constants reveal the extent of their unpaired spin distributions. Abstract : The reaction of H atoms with fullerene C70 has been investigated by identifying the radical products formed by addition of the atom muonium (Mu) to the fullerene in solution. Four of the five possible radical isomers of C70 Mu were detected by avoided level-crossing resonance (μLCR) spectroscopy, using a dilute solution of enriched 13 C70 in decalin. DFT calculations were used to predict muon and 13 C isotropic hyperfine constants as an aid to assigning the observed μLCR signals. Computational methods were benchmarked against previously published experimental data for 13 C60 Mu in solution. Analysis of the μLCR spectrum resulted in the first experimental determination of 13 C hyperfine constants in either C70 Mu or C70 H. The large number of values confirms predictions that the four radical isomers have extended distributions of unpaired electron spin.